Semi‐interpenetrating polymer network cryogels based on poly(ethylene glycol) diacrylate and collagen as potential off‐the‐shelf platforms for cancer cell research. Issue 9 (11th January 2021) - Masullo, Ugo; Cavallo, Anna; Greco, Maria Raffaella; Reshkin, Stephan J.; Mastrodonato, Maria; Gallo, Nunzia; Salvatore, Luca; Verri, Tiziano; Sannino, Alessandro; Cardone, Rosa Angela; Madaghiele, Marta
Abstract: In the present work, we investigated the potential of novel semi‐interpenetrating polymer network (semi‐IPN) cryogels, obtained through ultraviolet exposure of aqueous mixtures of poly(ethylene glycol) diacrylate and type I collagen, as tunable off‐the‐shelf platforms for 3D cancer cell research. We synthesized semi‐IPN cryogels with variable collagen amounts (0.1% and 1% w/v) and assessed the effect of collagen on key cryogel properties for cell culture, for example, porosity, degradation rate and mechanical stiffness. Then, we investigated the ability of the cryogels to sustain the long‐term growth of two pancreatic ductal adenocarcinoma (PDAC) cell populations, the parenchymal Panc1 cells and their derived cancer stem cells. Results revealed that both cell lines efficiently infiltrated, attached and expanded in the cryogels over a period of 14 days. However, only when grown in the cryogels with the highest collagen concentration, both cell lines reproduced their characteristic growth pattern previously observed in collagen‐enriched organotypic cultures, biomimetic of the highly fibrotic PDAC stroma. Cellular preembedding in Matrigel, that is, the classical approach to develop/grow organoids, interfered with an efficient intra‐scaffold migration and growth. Although preliminary, these findings highlight the potential of the proposed cryogels as reproducible and tunable cancer cell research platforms.